Advancing global health research through digital technology and sharing data. - Lang, T (2011)
The imperative for improving health in the world's poorest regions lies in research, yet there is no question that low participation, a lack of trained staff, and limited opportunities for data sharing in developing countries impede advances in medical practice and public health knowledge. Extensive studies are essential to develop new treatments and to identify better ways to manage healthcare issues. Recent rapid advances in availability and uptake of digital technologies, especially of mobile networks, have the potential to overcome several barriers to collaborative research in remote places with limited access to resources. Many research groups are already taking advantage of these technologies for data sharing and capture, and these initiatives indicate that increasing acceptance and use of digital technology could promote rapid improvements in global medical science.